Similar deficiencies, different outcomes: succinate dehydrogenase loss in adrenal medulla vs. fibroblast cell culture models of paraganglioma - Fatimah J. Al Khazal; Sanjana Mahadev Bhat; Yuxiang Zhu; Cristina M. de Araujo Correia; Sherry X. Zhou; Brandon A. Wilbanks; Clifford D. Folmes; Gary C. Sieck; Judith Favier; L. James Maher (Cancer & Metabolism)
Abstract Heterozygosity for loss-of‐function alleles of the genes encoding the four subunits of succinate dehydrogenase (SDHA, SDHB, SDHC, SDHD), as well as the SDHAF2 assembly factor predispose affected individuals to pheochromocytoma and paraganglioma (PPGL), two rare neuroendocrine tumors that arise from neural crest-derived paraganglia. Tumorigenesis results from loss of the remaining functional SDHx gene copy, leading to a cell with no functional SDH and a defective tricarboxylic acid (TCA) cycle. It is believed that the subsequent accumulation of succinate competitively inhibits multiple dioxygenase enzymes that normally suppress hypoxic signaling and demethylate histones and DNA, ultimately leading to increased expression of genes involved in angiogenesis and cell proliferation. Why SDH loss is selectively tumorigenic in neuroendocrine cells remains poorly understood. In the absence of SDH-loss tumor-derived cell models, the cellular burden of SDH loss and succinate accumulation have been investigated through conditional knockouts of SDH subunits in pre-existing murine or human cell lines with varying degrees of clinical relevance. Here we characterize two available murine SDH-loss cell lines, immortalized adrenally-derived premature chromaffin cells vs. immortalized fibroblasts, at a level of detail beyond that currently reported in the literature and with the intention of laying the foundation for future investigations into adaptive pathways and vulnerabilities in SDH-loss cells. We report different mechanistic and phenotypic manifestations of SDH subunit loss in the presented cellular contexts. These findings highlight similarities and differences in the cellular response to SDH loss between the two cell models. We show that adrenally-derived cells display more severe morphological cellular and mitochondrial alterations, yet are unique in preserving residual Complex I function, perhaps allowing them to better tolerate SDH loss, thus making them a closer model to SDH-loss PPGL relative to fibroblasts. (281 words)